Scenario Based Modelling of Water Resource Resilience through Coupled Hydrologic and Demand Forecast Systems in Tehran and Desert Edge Settlements (Scientific Journal of Research Studies in Future Civil Engineering, 2025)
This study develops a scenario-based modelling framework to evaluate the resilience of urban water resources in Tehran and selected desert-edge settlements, where chronic water scarcity has intensified due to accelerating climate variability. The approach integrates hydrologic simulation with long-term water demand forecasting to capture the dynamic interactions between climate-driven supply constraints and urban consumption patterns. Hydrologic projections are generated through multi-model climate inputs to assess future inflows, groundwater variability, and drought recurrence, while demand forecasts incorporate demographic growth, seasonal variations, socioeconomic trends, and nonlinear consumption behaviour. By coupling these two components, the model quantifies resilience trajectories under multiple future scenarios, including baseline, moderate climate stress, and severe drought intensification. The research applies this integrated system to Tehran as a megacity highly dependent on surface reservoirs and vulnerable aquifers, alongside desert-edge settlements where rising temperatures and reduced recharge rates sharply limit resource flexibility. Resilience indicators are constructed to evaluate adaptive capacity, reliability thresholds, environmental flow protection, and spatial vulnerability across the study region. Scenario simulations reveal strong divergence between supply and demand pathways, with severe climate stress producing marked reductions in groundwater storage and a sharp decline in system reliability. Conversely, scenarios incorporating adaptive allocation, conservation policies, and optimized demand management exhibit measurable improvements in long-term resilience. The findings demonstrate that coupling hydrologic and demand-forecast systems significantly enhances the predictive clarity needed for policymaking in water-stressed regions. The model highlights the urgent need for integrated planning, prioritization of climate-smart interventions, and the adoption of adaptive water-allocation frameworks to sustain future urban viability. This framework provides a replicable foundation for resilience assessment in other arid and semi-arid urban environments and contributes to bridging the gap between climate projections, hydrologic processes, and decision-oriented water-management strategies.